STUDY OF PRESCRIBING PATTERN IN ELDERLY PATIENTS VISITING MEDICINE OUTPATIENT DEPARTMENT AT A TERTIARY CARE HOSPITAL - POORWA WANDALKAR; P.T. PANDIT; B.B. GHONGANE (International Journal of Pharma and Bio Sciences, 2015)
Elderly have pathophysiological changes, higher incidence of chronic diseases, are at risk of polypharmacy and medication errors. Drug utilisation studies enable us to detect such problems and prioritize efforts to correct them. The current study was carried out with the objectives of delineating prescription pattern in elderly outpatients, determining the prescribing frequency of Potentially Inappropriate Medications (PIMs) according to Beers criteria and evaluating prescriptions according to WHO indicators. Prescriptions of elderly patients visiting Medicine OPD were collected over a year. Hypertension was the commonest diagnosis, Ranitidine the most frequently prescribed medication. PIMs were minimal (1.26%). On average, 3.7 drugs were prescribed per patient. 95.79% were prescribed by generic name, 94.53% from Essential drug list. Percentage of encounters with antibiotic prescribed was 13.9%. Prescription pattern was rational with respect to WHO indicators. Lacunae like overuse of multivitamins, prescription of PIMs came forth. More studies in other specialties are necessary to sensitize practitioners towards rational prescribing.